Client Perspectives of Telerehabilitation in Stuttering during the Covid-19 Pandemic: A Survey at a Tertiary Rehabilitation Center in Kerala - Preethy Susan Reni; Vrinda R; Rejitha Kumari L; Suja Kunnath (Journal of Rehabilitation Sciences and Research, 2025)
Background: Studies on telerehabilitation in India have primarily addressed the clinicians’ perspective. Therefore, this study aimed to understand the perspectives of clients—specifically adults who stutter—regarding telerehabilitation during the COVID-19 pandemic. Method A mixed-methods survey, combining interviews and self-report questionnaires, explored client perspectives on telerehabilitation for adults who stutter during the pandemic. Twelve adults who stutter aged 18 to 40 attending telerehabilitation sessions at a tertiary rehabilitation center participated in the study. Results All participants expressed comfort in discussing their problems and anxieties with the clinician during teletherapy sessions. Additionally, 91.7% (n = 11) reported feeling confident in managing the online platform. Of the participants, 66.7% (n = 8) rated the sessions as excellent, while 33.3% (n = 4) rated them as good. Preferences regarding session modes were evenly split, with 50% favoring teletherapy and the other 50% preferring a hybrid approach. The majority of participants considered avoiding travel during the pandemic to be a significant advantage of telerehabilitation. However, internet connectivity issues were identified as a major disadvantage. Conclusion The findings of this study highlight both the advantages and challenges of telerehabilitation for adults who stutter. Participants reported that telerehabilitation helped improve their speech fluency and proved a viable and effective approach for addressing stuttering during the COVID-19 pandemic.